2022
DOI: 10.1108/ajim-08-2021-0235
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to entry of gig workers in the gig platforms: exploring the dark side of the gig economy

Abstract: PurposeThe alternative arrangements to traditional employment have become a promising area in the gig economy with the technological advancements dominating every work. The purpose of this paper is to explore the barriers to the entry of gig workers in gig platforms pertaining to the food delivery sector. It proposes a framework using interpretive structural modelling (ISM) for which systematic literature review is done to extract the variables. This analysis helps to examine the relationship between the entry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The third subcode under power asymmetry, social isolation, only mentioned in 24% of the papers, has more been studied through a psychological lens, and these papers were excluded from this SLR, so there is work to be done examining social isolation from a socio‐technical perspective. As most of the studies in industrial and organizational psychology were conducted in a traditional workplace, it would be interesting to investigate job satisfaction, motivation (Pogorevici & Serobe, 2020), burnout, and well‐being in the context of digital workplaces (Parent‐Rocheleau & Parker, 2022), and how those issues could interact with issues of technical design (Behl, Rajagopal, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third subcode under power asymmetry, social isolation, only mentioned in 24% of the papers, has more been studied through a psychological lens, and these papers were excluded from this SLR, so there is work to be done examining social isolation from a socio‐technical perspective. As most of the studies in industrial and organizational psychology were conducted in a traditional workplace, it would be interesting to investigate job satisfaction, motivation (Pogorevici & Serobe, 2020), burnout, and well‐being in the context of digital workplaces (Parent‐Rocheleau & Parker, 2022), and how those issues could interact with issues of technical design (Behl, Rajagopal, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of surveillance also happened during the COVID-19 pandemic, while the platforms imposed strict hygiene protocols for workers, for example, a daily temperature update and rigorous sanitization measures during the task performance (Anjali Anwar et al, 2022). Algorithmic control (B13) refers to the case in which gig economy platforms leverage their user interfaces, experience designs, and data about gig workers to exercise control over their work (Behl, Rajagopal, et al, 2022). For example, workers must maintain a persistent connection to the platform, running up data costs, working under conditions of continuous monitoring (Newlands, 2022), having less control over the jobs for which they can compete (Polkowska & Mika, 2022), and submitting to human resource activities that control their work, such as accepting sanctions based on the rating system and constraints on their decision-making (Ens et al, 2018).…”
Section: Platform Governancementioning
confidence: 99%
“…Besides, riders will base on the autonomy level, job market vulnerability and economic attachment of the food delivery platform to select the employment status and work schedule. Behl et al (2022) concluded that the major obstacles of being a rider include high competition as well as long login hours and late-night delivery services provision, followed by poor remuneration and unfavorable conditions for getting incentives. Moreover, Puram et al (2021) found that rider faces different work pressures and difficulties especially during the COVID-19 pandemic, including operational, customer-related, organizational, and technological issues.…”
Section: Work Conditionsmentioning
confidence: 99%
“…Scholars have moved beyond an exclusive focus on the labour process that characterised early gig economy scholarship, broadening their scope to encompass many migration-specific factors. For example, these include institutional barriers for migrants seeking entrance to national labour markets (Behl et al, 2022); migrants’ different pathways into platform work (Orth, 2024); and the role of emerging migrant-led indie unions (Però and Downey, 2024) – each reflecting the specific challenges and opportunities that migrants face when trying to earn an income in the gig economy. This research shows that migrant gig work is always the outcome of a complex interplay between institutional (dis)embeddedness, personal and professional life trajectories, and (self-)organised forms of labour struggle.…”
Section: Introductionmentioning
confidence: 99%